SAT-409 A Novel Population of Kisspeptin Neurons in the Medial Tuberal Nucleus of the Hypothalamus in Mice - Stephens, Shannon (J Endocr Soc, 2019)
Kisspeptin, encoded by Kiss1, stimulates GnRH release and is required for puberty onset and reproduction. Kiss1 neurons primarily reside in the hypothalamus, in the AVPV/PeN and ARC nuclei; however, smaller Kiss1 neuronal populations exist in other regions such as the medial amygdala, bed nucleus of the stria terminalis, and lateral septum. We identified a novel population of Kiss1 neurons in the lateral hypothalamus, specifically in the medial tuberal nucleus (MTu), in mice. A similar, small population of Kiss1 neurons in this lateral hypothalamic region was also newly identified in sheep (Moore et al., 2018), but nothing is known about the regulation or function of these Kiss1 neurons. Using both in situ hybridization in normal mice and fluorescent TdTomato expression in KissCre+/TdTomato+ mice, we confirmed the presence of Kiss1 neurons in the MTu of adult mice. Next, we examined the developmental time course of Kiss1 expression in the MTu by looking at TdTomato expression in KissCre+/TdTomato+ mice at different developmental ages (prepubertal, pubertal, and adult). We found that TdTomato expression in the MTu increased around puberty, perhaps as a result of increasing gonadal sex steroids. Estradiol (E(2)) regulates Kiss1 expression in all previously-identified Kiss1 neuronal populations and thus, we next examined whether E(2) regulates MTu Kiss1 expression. We found that like the AVPV and extra-hypothalamic Kiss1 populations, Kiss1 expression in the MTu is upregulated by E(2). In addition to E(2), GABA(B)R signaling is known to regulate extra-hypothalamic Kiss1 expression, while having no impact on AVPV/PeN and ARC Kiss1 expression. We examined if GABA(B)R signaling regulates MTu Kiss1 expression by comparing Kiss1 expression in WT and GABA(B)R KO mice. Like the other hypothalamic Kiss1 populations in the AVPV and ARC, Kiss1 expression in the MTu does not appear to be strongly regulated by GABA(B)R signaling in male mice. Additional research is ongoing to further characterize these E(2)-regulated MTu Kiss1 neurons and elucidate their function(s).